Interventions on children’s and adolescents’ physical activity and sedentary behaviour: protocol for a systematic review from a sex/gender perspective - Demetriou, Yolanda; Vondung, Catherina; Bucksch, Jens; Schlund, Annegret; Schulze, Carolin; Knapp, Guido; Coen, Stephanie E.; Puil, Lorri; Phillips, Susanne P.; Reimers, Anne Kerstin (Systematic Reviews, 2019)
Low levels of physical activity (PA) and high levels of sedentary behaviour (SB) have been observed in young people. Both behaviours are detrimental for health with patterns tending to continue into adulthood. There is sustained value in establishing health habits in early years. Even though levels of SB and participation in PA differ among boys and girls, and the effectiveness of interventions to promote PA and/or prevent sedentary behaviours varies by sex/gender to date, sex/gender in systematic reviews is not yet widely considered. Additionally, while tools have been proposed, there is no consensus on the criteria to assess sex/gender in systematic reviews in the context of health promotion. The main objectives of this systematic review are to evaluate the effects of interventions on girls’ and boys’ PA and SB and to appraise the extent to which the studies have taken sex/gender into account.
Keywords: PRISMA-P; Girls; Boys; Randomized controlled trial; Youth; Cochrane; Exercise